Identification of novel Tet(X6)-Tet(X2) recombinant variant in Elizabethkingia meningoseptica from a bullfrog farm and downstream river in China - Jin, Haobo; Jia, Qing; Jin, Xi; Zhu, Xinlong; Wang, Min-Ge; Sun, Ruan-Yang; Cui, Chaoyue (Frontiers in Microbiology, 2024)
Introduction The dissemination of strains producing tetracyclines monooxygenase Tet(X) from breeding farms to the natural environment poses a potential threat to public health. Methods Antimicrobial susceptibility testing and WGS were performed to identify resistance phenotypes and genotypes. Cloning experiments, sequence alignment, and homology modeling were used to characterize the function and formation mechanisms of the recombinant variant. The mobilization potential of Tet(X) was assessed by collinearity analysis, conjugation experiments, and phylogenetic analysis. Results Three tet(X)-producing Elizabethkingia meningoseptica strains were isolated from bullfrog breeding ponds, the sewage outlet, and downstream river in Zhejiang Province, China. These strains carry a novel Tet(X) variant, differing from Tet(X6) by seven residues, and possess the ability to degrade tetracyclines. Interestingly, the novel Tet(X) is a recombinant variant formed by homologous recombination of Tet(X6) and the C-terminal of Tet(X2). Further analysis revealed that Tet(X6) formed several Tet(X) variants, including Tet(X5), through homologous recombination. The novel tet(X) gene is located on a circularizable integrative and conjugative element (ICEEmeChn3), with ISwz1 participating in the recombination of its multi-drug resistance region, potentially facilitating the mobilization and recombination of tet(X) in early hosts. These three strains were clonally transmitted and shared a close genetic relationship (SNP < 62) with a clinically-sourced strain isolated from the same province. Discussion To our knowledge, this is the first report of homologous recombination between Tet(X) variants with differing activities. These clonal strains provide evidence of the transmission of tet(X)-positive strains from aquaculture sewage to the natural environment, highlighting the need to strengthen the monitoring and management of this emerging farming model.